2019
DOI: 10.2174/1381612825666190110144254
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic and Predictive Value of microRNAs in Patients with H. pylori-positive Gastric Cancer

Abstract: Gastric cancer (GC) has a high mortality rate with a poor 5-year survival. Helicobacter pylori (H. pylori) is present as part of the normal flora of stomach. It is found in the gastric mucosa of more than half of the world population. This bacterium is involved in developing H. pylori-induced GC due to the regulation of different micro ribonucleic acid (miRNA or miR). miRNAs are small noncoding RNAs and are recognized as prognostic biomarkers for GC that may control gene expression. miRNAs may function as tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…H. pylori is the primary human pathogen in the gastric mucosa of almost half of the global population, which participates in developing GC through the regulation of miRNA expression. miRNAs have been noticed as prognostic biomarkers in GC due to their gene regulatory role in cells, such as tumor suppressors and promoter functions [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori is the primary human pathogen in the gastric mucosa of almost half of the global population, which participates in developing GC through the regulation of miRNA expression. miRNAs have been noticed as prognostic biomarkers in GC due to their gene regulatory role in cells, such as tumor suppressors and promoter functions [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant regulation of miRNAs can function as oncogenes or anti-oncogenes by binding with its specific target mRNAs, resulting in mRNA degradation or/and translational repression (9). Studies have revealed the regulatory roles of miRNAs in H. pylori-induced inflammation and carcinogenesis (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are involved in a variety of cellular processes, from embryonic development and immunity to carcinogenesis, by interacting with their multiple targets [4]. MiRNAs also play a vital role in the pathogenesis of gastric cancer [5,6]. MicroRNA-155 (miR-155) is a multifunctional miRNA that is involved in many disease processes including hematopoietic development [7,8], inflammatory responses [9,10], autoimmune [11], and tumorigenesis [12,13].…”
Section: Introductionmentioning
confidence: 99%